Multiple pathways of SARS-CoV-2 nosocomial transmission uncovered by integrated genomic and epidemiological analyses during the second wave of the COVID-19 pandemic in the UK - Cook, Kate F.; Beckett, Angela H.; Glaysher, Sharon; Goudarzi, Salman; Fearn, Christopher; Loveson, Katie F.; Elliott, Scott; Wyllie, Sarah; Lloyd, Allyson; Bicknell, Kelly; Lumley, Sally; Chauhan, Anoop J.; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Throughout the global COVID-19 pandemic, nosocomial transmission has represented a major concern for healthcare settings and has accounted for many infections diagnosed within hospitals. As interventions in response to the pandemic begin to ease, it is important to uncover the specific pathways by which nosocomial outbreaks occur to understand the most suitable transmission control strategies for the future. In this investigation, SARS-CoV-2 genome sequences obtained from 694 healthcare workers and 1,181 patients at Queen Alexandra Hospital (QAH), Portsmouth, UK throughout the second wave of the pandemic were analyzed. These viral genomic data were combined with epidemiological data to uncover transmission routes within the hospital. We also investigated the effects of the introduction of the highly transmissible variant of concern (VOC), Alpha, over this period, as well the effects of the national vaccination program on SARS-CoV-2 infection in the hospital. Our results show that infections of all variants within the hospital increased as community prevalence of Alpha increased, resulting in several outbreaks and super-spreader events. Nosocomial infections were enriched amongst older and more vulnerable patients more likely to be in hospital for longer periods but had no impact on patient severity. Infections appeared to be transmitted most regularly from patient to patient and from patients to HCWs. In contrast, infections from HCWs to patients appeared rare, highlighting the benefits of PPE in infection control. The introduction of the vaccine at this time also reduced infections amongst HCWs by over four-times. These analyses have highlighted the importance of control measures such as regular testing, rapid lateral flow testing alongside polymerase chain reaction (PCR) testing, isolation of positive patients in the emergency department (where possible), and physical distancing of patient beds on hospital wards to minimize nosocomial transmission of infectious diseases such as COVID-19.